Generation of one iPSC line (IMEDEAi006-A) from an Early-onset Familial Alzheimer's Disease (fAD) Patient Carrying the E280A Mutation in the PSEN1 Gene (2019)
ABSTRACT: The mutation E280A in PSEN1 (presenilin-1) is the most common cause of early-onset familial Alzheimer's Disease (fAD). It presents autosomal dominant inheritance and frequently leads to the manifestation of the disease in relatively young individuals. Here we report the generation of one PSEN1 E280A iPSC line derived from an early-onset patient. OriP/EBNA1-based episomal plasmids containing OCT3/4, SOX2, KLF4, L-MYC, LIN28, BCL-xL and shp53 were used to reprogram oral mucosa fibroblasts. The iPSC line generated has normal karyotype, carry the E280A mutation, is free of plasmid integration, express high levels of pluripotency markers and can differentiate into all three germ layers.